Potential effects of underwater noise from wind turbines on the marbled rockfish (Sebasticus marmoratus). (27th March 2021) - Zhang, Xuguang; Guo, Hongyi; Chen, Jia; Song, Jiakun; Xu, Kaida; Lin, Jun; Zhang, Shouyu
Abstract: Environmental assessments of underwater noise on marine species must be based on species‐specific hearing abilities. This study was to assess the potential impact of underwater noise from the East China Sea Bridge wind farm on the acoustic communication of the marbled rockfish. Here, the 1/3 octave frequency band of underwater noise was 125 Hz with the level range of 78–96 dB re 1 μPa, recorded at distances between 15‐20m from the foundation at wind speed of 3–5 m/s. Auditory evoked potential (AEP) and passive acoustic techniques were used to determine the hearing abilities and sound production of the fish. The resultes showed the lowest auditory threshold of Sebastiscus marmoratus was 70 dB at 150 Hz matching the disturbance sound ranging 140–180 Hz, which indicating the acoustic communication used in this species. However, the frequency and level of turbine underwater noise overlapped the auditory sensitivity and vocalization of Sebastiscus marmoratus . The wind turbine noise could be detected by fish and may have a masking effect on their acoustic communication. This result can be applied for further to the assessent of fish species released into offshore wind farm marine ranch.